Turning Big Brother upside down: Revisiting surveillance from Latin America. Issue 11 (26th October 2021) - Ragas, José
Abstract: This essay discusses the emergence of a vibrant body of research embracing surveillance in Modern Latin America. By focusing on a specific yet complex region, scholars have expanded the original framework associated with the term, applying this new lens to periods ranging from after the Wars of Independence to contemporary episodes. Moreover, the examination of surveillance in this region reveals how researchers have engaged not only with trending research but their willingness to respond to the social, political, and technological phenomena that have become more visible since the 9/11 terrorist attacks and the implementation of a new paradigm based on state security. This concern has become augmented with the revelations on the role of the National Security Agency and social media companies obtaining data from citizens. I conclude by suggesting new avenues for this nascent scholarship to move away from its rigid Orwellian nature and turn surveillance into a more flexible analytical tool.